The Oxford handbook of Buddhist ethics - Cozort, Daniel 1953-; Shields, James Mark (Oxford Oxford University Press, 2018)
A comprehensive overview of the study of Buddhist ethics in the twenty-first century.
Series statement from book jacket.
Includes bibliographical references and index.
Keywords: Buddhist ethics